La spugna è la mia anima Omaggio a Piero Ceccucci - Barbara Gori (Studi e saggi, 2016)
La spugna è la mia anima. Omaggio a Piero Ceccucci ("The sponge is my soul. Tribute do Pietro Ceccucci") is a work born from the sincere affection and esteem of many Italian and foreign colleagues who enthusiastically welcomed the idea of paying homage to their friend and colleague Piero Ceccucci and to his long career as a university professor of Portuguese and Brazilian language and literature at various Italian universities, such as Perugia, Milan, University "Bocconi" of Milan, Genoa and Florence. This volume aims to be a fair recognition of the commitment and dedication that Prof. Piero Ceccucci has addressed to the teaching of Portuguese language and literature in Italy, but also to remind him the gratitude of University of Florence, to which, we are sure, he will always be tied.